Analysis of impact of climate change on growth and yield of yam and cassava and adaptation strategies by farmers in Southern Nigeria - Chukwuone, Nnaemeka (International Food Policy Research Institute, 2015)
This study determined the adaptation and coping strategies adopted by farmers under yam- and cassava-based farming systems in Ebonyi and Enugu States in Nigeria’s derived savannah agro-ecological zone. The study uses data from 400 farmers. The likelihood that the farmers engage in some actions to cushion the effect of climate change was determined using a probit model and a multi-nomial logistic regression. The results of the study revealed that the main outcomes of climate change were flooding (71.29%), decline in crop yields (65.1%), food price increases (62.87%), and food shortages/insecurity (57.92%). The average amount of loss to climate change was N164,318.8 naira. To cushion the effect of climate change, the highest proportion (45.05%) of the farmers bought food. In terms of land management practices used, the majority (74.34%, 83.55%, 72.37%, and 60.53%) of the farmers keep their land under fallow, mulch/use surface cover, intercrop, and use farmyard manure, respectively. Number of years in school and household size significantly influence the likelihood of a farmer starting non-farm activity to cushion the effect of climate change. Age, gender of household head, and amount of loss due to climate change significantly influence the decision to plant pest- and disease-resistant crops to cushion climate change effects. Thus, policies to encourage planting of these crops should focus more on male-headed households and on households that have experienced some previous losses due to climate change since they will be more likely to grab any opportunity that will prevent any further loss.